Nitric Oxide Synthase: Non-Canonical Expression Patterns - Mattila, Joshua T.; Thomas, Anita C. (Frontiers in Immunology, 2014)
Science can move ahead by questioning established or canonical views and, so it may be with the enzymes, nitric oxide synthases (NOS). Nitric oxide (NO) is generated by NOS isoforms that are often described by their tissue-specific expression patterns. NOS1 (nNOS) is abundant in neural tissue, NOS2 is upregulated in activated macrophages and known as inducible NOS (iNOS), and NOS3 (eNOS) is abundant in endothelium where it regulates vascular tone. These isoforms are described as constitutive or inducible, but in this Perspective we question the broad application of these labels. Are there instances where ‘constitutive’ NOS (NOS1 and NOS3) are inducibly expressed; conversely, are there instances where NOS2 is constitutively expressed? NOS1 and NOS3 inducibility may be linked to post-translational regulation, making their actual patterns activity much more difficult to detect. Constitutive NOS2 expression has been observed several tissues, especially the human pulmonary epithelium where it may regulate airway tone. These data suggest expression of the three NOS enzymes may include non-established patterns. Such information should be useful in designing strategies to modulate these important enzymes in different disease states.